Microduplication of 3p26.3 in Nonsyndromic Intellectual Disability Indicates an Important Role of CHL1 for Normal Cognitive Function - Shoukier, Moneef; Fuchs, Sigrid; Schwaibold, Eva; Lingen, Michael; Gärtner, Jutta; Brockmann, Knut; Zirn, Birgit (Neuropediatrics, 2013)
Terminal deletions of chromosome 3p26.3 confined to the CHL1 gene have previously been described in children with intellectual disability and epilepsy. Here, we report for the first time, a 3p26.3 duplication including only the CHL1 gene in an intellectually disabled girl with epilepsy. The penetrance of both deletions and duplications in 3p26.3 is reduced because all chromosomal imbalances were inherited from healthy parents. Further studies are needed to specify the pathogenic mechanism of 3p26.3 imbalances and to estimate recurrence risks in genetic counseling. However, the description of both deletions and duplications of chromosome 3p26.3 in nonsyndromic intellectual disability suggests that CHL1 is a dosage-sensitive gene with an important role for normal cognitive development.
Keywords: chromosomal duplication; intellectual disability; epilepsy; CHL1 gene